2019
DOI: 10.4209/aaqr.2019.10.0540
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization Performance of Rare Earth Mono-substituted Heteropoly Compounds

Abstract: In this study, a series of rare earth monosubstituted Dawson-type polyoxometalates were synthesized for highly effective removal of hydrogen sulfide (H 2 S). The unused, used and regenerated polyoxometalates were characterized by Fourier transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS). The results confirmed that K 17 [Pr(P 2 Mo 17 O 61) 2 ] could maintain a complete Dawson-type structure even after absorption and regeneration. H 2 S absorption study showed that K 17 [Pr(P 2 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In Pr 3d spectrum, two peaks at 931.6 and 974.5 eV can be ascribed to Pr 3d 5/2 (Pr 4+ ) and Pr 3d 3/2 (Pr 4+ ) respectively. One satellite peak due to Pr 3d 3/2 is seen at 981.4 eV [40,41] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Pr 3d spectrum, two peaks at 931.6 and 974.5 eV can be ascribed to Pr 3d 5/2 (Pr 4+ ) and Pr 3d 3/2 (Pr 4+ ) respectively. One satellite peak due to Pr 3d 3/2 is seen at 981.4 eV [40,41] …”
Section: Resultsmentioning
confidence: 99%
“…One satellite peak due to Pr 3d 3/2 is seen at 981.4 eV. [40,41] To validate the influence of TM-RE HEO in polysulfide entrapment in LSBs, the electrochemical properties of TM-RE HEO are evaluated. Cyclic voltammetry (CV) curves of three samples are presented in Figure 3(a).…”
Section: Resultsmentioning
confidence: 99%
“…), and oxygen atoms in certain spatial structure . Due to their unique structure and properties, HPCs have shown broad application prospects in many fields. , In terms of desulfurization, HPCs have been in the field of H 2 S removal due to its strong oxidative, easy regeneration performance, and strong stability. Based on reports, HPCs were dissolved in ILs to obtain HPC/IL solutions. The desulfurization and regeneration performance of HPC/IL solutions were investigated; it was found that they have excellent desulfurization and regeneration performance at high temperatures.…”
Section: Introductionmentioning
confidence: 99%